A proteoglycan isolated from Ganoderma lucidum attenuates diabetic kidney disease by inhibiting oxidative stress-induced renal fibrosis both in vitro and in vivo. (28th June 2023) - Pan, Yanna; Zhang, Ying; Li, Jiaqi; Zhang, Zeng; He, Yanming; Zhao, Qingjie; Yang, Hongjie; Zhou, Ping
Abstract: Ethnopharmacological relevance: Ganoderma lucidum ( G. lucidum ) was regarded as "miraculous herb" by the Chinese and recorded detailly in the "Shen Nong Ben Cao Jing" as a tonic to improve health and prolong life. A proteoglycan (namely, FYGL ) was extracted from Ganoderma lucidum, which was a water-soluble hyperbranched proteoglycan, and was found to be able to protect pancreatic tissue against oxidative stress damage. Aim of the study: Diabetic kidney disease (DKD) is a complication of diabetes, but the effective treatment is still lack. Chronic hyperglycemia in diabetic patients induce the accumulation of ROS, which injure the renal tissue and lead to the renal dysfunction. In this work, the efficacy and target mechanics of FYGL on diabetic renal function were investigated. Materials and methods: In the present study, the mechanism of the reno-protection of FYGL was analyzed on diabetic db/db mice and rat glomerular mesangial cells (HBZY-1) induced by high glucose (HG) with palmitate (PA) (HG/PA). In vitro, the levels of reactive oxygen species (ROS), malondialdehyde (MDA) and superoxide dismutase (SOD) were evaluated by commercial kits. the expressions of NOX1 and NOX4, phosphorylation of MAPK and NF-κB, and pro-fibrotic proteins were measured by Western blot. In vivo, diabetic db/db mice were gavaged with FYGL for 8 weeks, body weight and fasting blood glucose (FBG) were tested weekly. On 8th week, the serum, urine and renal tissue were collected for glucose tolerance test (OGTT), redox indicator (SOD, CAT, GSH and MDA), lipid metabolism (TC, TG, LDL and HDL), blood urea nitrogen (BUN), serum creatinine (Scr), uric acid (UA), 8-oxo-deoxyguanosine (8-OHdG), and the changes of histopathology and expression of collagen IV and AGEs. Results: The results in vitro showed that FYGL significantly inhibited the HG/PA-induced HBZY-1 cells proliferation, ROS generation, MDA production, promoted SOD activity, and suppressed NOX1, NOX4, MAPK, NF-κB, and pro-fibrotic proteins expression. In addition, FYGL markedly alleviated blood glucose, antioxidant activity and lipid metabolism, improved renal functions, and relieved renal histopathological abnormalities, especially renal fibrosis. Conclusions: The antioxidant activity of FYGL can reduce ROS caused by diabetes and protect renal from oxidative stress-induced dysfunction, thereby improving renal function. This study shows that FYGL has the potential to treat diabetic kidney disease. Graphical abstract: Schematic diagram showing the mechanism of FYGL in alleviating diabetic kidney disease. Image 1 Highlights: FYGL ameliorate the blood glucose and renal dysfunction in vivo. FYGL reduced diabetes-induced ROS because of its antioxidant activity. FYGL inhibit glomerulosclerosis and renal fibrosis to prevent diabetic nephropathy.